#TITLE_ALTERNATIVE# - SYARIF MAHFUD (NIM : 13706057); Pembimbing : Dr. Ir. Husaini Ardy, MUHAMMAD
Blade compressor as one of most important component of gas turbine is operated at relatively high temperature, corrosive environment and susceptible of creep phenomenon. All of those factors are related to time – temperature condition. The life of compressor is often determined by the life of its blades. Thus, the life assessment about time and operating temperature becomes an important thing to do. Many research about life assessment have already been done today, one of the most common model about it is Hollomon – Jaffe parameter. The Hollomon – Jaffe parameter connects the time – temperature relation to the mechanical properties. This research studies about the behaviour of mechanical properties and microstructure of X20 CRMoV12-1 steel at certain time and temperature. The temperature used in this research are 400, 450 and 500°C and the time of heating are 6, 12 dan 24 hours. With those parameters, the life assessment of the blade can be predticted using the Hollomon – Jaffe’s method. The lowest hardness of all parameters is 25.2 HRC for R1-8 and 25.7 HRC for R4-19. The tensile tests for those blades are examined under two conditions, without heating (TP condition) and by heating (PM condition). The result of tensile strength at TP condition is 925.8 MPa for R1-8 and 952.6 MPa for R4-19. The tensile strength at PM condition is 927.3 MPa for R1-8 and 955.7 MPa for R4-19. By using the Hollomon – Jaffe’s method R1-8 is predicted to have 1958.44 hours remaining, while R4-19 have 35481.33 hours remaining.